2019
DOI: 10.1016/j.heliyon.2019.e02884
|View full text |Cite
|
Sign up to set email alerts
|

Importance and share of agribusiness in the Chinese economy (2000–2014)

Abstract: This paper analyzes the importance and share of agribusiness and its aggregates in the Chinese national economy in the context of economic growth observed in 2000–2014. Based on National Input-Output Tables (NIOT) data, the share of agribusiness in Gross Domestic Product (GDP), employment, and global output was found to have declined due to a decrease in the share of agriculture itself. Hence, the increase in agribusiness GDP was primarily driven by the supply-related aggregate. In turn, the food industry prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Due to the release of labor to other sectors of the economy, labor is substituted by capital in agriculture. This leads to a situation in which, after this process is concluded, an increase in intermediate consumption is necessary to increase output [ 45 ]. Intuitively, a similar situation should be expected in the case of the relationship between the material intensity of the food industry and the emission intensity of food production systems; however, in this case, the obtained results were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the release of labor to other sectors of the economy, labor is substituted by capital in agriculture. This leads to a situation in which, after this process is concluded, an increase in intermediate consumption is necessary to increase output [ 45 ]. Intuitively, a similar situation should be expected in the case of the relationship between the material intensity of the food industry and the emission intensity of food production systems; however, in this case, the obtained results were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the emission intensity of food production, the global output of food production was calculated using the Mrówczyńska-Kamińska and Bajan [ 45 ] method. This method assumes that food production consists the agriculture activities, the food industry activities, and other sectors’ activities that deliver inputs and services to agriculture and the food industry.…”
Section: Methodology and Datamentioning
confidence: 99%
“…An inverse way of looking at this indicator would be how many economic units of GDP are produced by the consumption of units of energy, which is a definition of economic energy efficiency-the indicator commonly used in national statistics and energy efficiency research [61]. In order to calculate the energy intensity of food production systems, we followed Mrówczyńska-Kamińska and Bajan's [62] method, which is consistent with the developed method of calculating food production energy use. It allows us to calculate the GDP of each of three food production aggregates.…”
Section: Methodsmentioning
confidence: 99%
“…These educational fields provide students with a wide range of competencies, which enables them to undertake various types of work in widely-understood agribusiness. In Poland, this sector employs more than 20% of the total workforce and generates 6.6% of the gross value added [24]. Due to its complexity, it generates employment not only in food production, processing, distribution and consumption areas but also in clothing production as well as storage and shelter space solutions [1].…”
Section: Rural Areas As Places Of Employment--theoretical Backgroundmentioning
confidence: 99%
“…The first stage involved performing a Mann-Whitney U test, which showed that experience has a significant impact (p < 0.05) only in the case of three features, i.e., irregular working hours (7), social benefits received (12) and working alongside competent colleagues (24). A Wald-Wolfowitz runs test was also performed, and in this case, experience turned out to be significant for the evaluation of five features of an ideal job, i.e., high task variability (4), irregular working hours (7), skill improvement opportunities (17), combining private and professional life in a relatively seamless way (20) and a sense of pride in one's work (28).…”
Section: The Attractiveness Of Agribusiness Jobs From a Gender Perspectivementioning
confidence: 99%